Strategi Guru Menumbuhkan Minat Belajar Pendidikan Agama Islam Bagi Siswa Difabel Tunalaras - Rahmanto, Azhar (JIE (Journal of Islamic Education), 2022)
The purpose of this study was to find out what strategies have been used by PAI teachers in growing interest in learning Islamic Religious Education at SLB E Prayuana. This research is a descriptive qualitative research based on field research. Data collection methods used in this study are observation methods, interview methods, and documentation. Data analysis used in this research is descriptive analytical method. The results of this study indicate that the learning interest of mentally retarded students at SLB E Prayuwana Yogyakarta is quite low. However, sometimes students can appear interested in the lesson if the factors that influence student interest are in good condition, such as students not having problems before entering school or entering class, students feel comfortable being with the teacher in the classroom, a supportive environment (nothing is distracting), students have experience about the material being taught, students are curious about what the teacher is teaching. The strategy used by the teacher to foster interest in learning for mentally retarded students at SLB E Prayuwana Yogyakarta is to apply the CTL and PAIKEM strategies.